2, 4, 6-Tribromophenol Disposition and Kinetics in Pregnant and Nursing Sprague Dawley Rats. (11th August 2020) - Knudsen, Gabriel A; Chapman, Margaret; Trexler, Andrew W; Juberg, Christopher T; Birnbaum, Linda S
Abstract: 2, 4, 6-Tribromophenol (TBP, CAS no. 118-79-6) is a brominated chemical used as a precursor, flame retardant, and wood antifungal agent. TBP is detected in environmental matrices and biota, including human breast milk, placenta, and serum. To address reports of TBP accumulation in human placenta and breast milk, studies were conducted to characterize TBP disposition and toxicokinetics in timed-pregnant or nursing Sprague Dawley rats following a single oral dose to the dam. Animals were administered [ 14 C]-TBP (10 μmol/kg, 25 µCi/kg, 4 ml/kg) by gavage on gestation day 12 and 20, or postnatal day 12 and serially euthanized between 15 min and 24 h for collection of blood and tissues from the dam and fetuses/pups. Observed plasma TBP C max (3 and 7 nmol/ml) occurred at 15 min in both GD12 and GD20 dams while C max (3 nmol/ml) was observed at 30 min for PND12 dams. Concentrations in tissues followed plasma concentrations, with kidneys containing the highest concentrations at 30 min. GD12 litters contained a sustained 0.2%–0.3% of the dose (5–9 nmol/litter) between 15 min and 6 h while GD20 fetuses (2%–3%) and placentas (0.3%–0.5%) had sustained levels between 30 min and 12 h. The stomach contents (approx. 1 nmol-eq/g, 6–12 h), livers (0.04–0.1 nmol-eq/g) and kidneys (0.1–0.2 nmol-eq/g) of PND12 pups increased over time, indicating sustained exposure via milk. Systemic exposure to TBP and its metabolites occurs in both the directly exposed mother and the indirectly exposed offspring and is rapid and persistent after a single dose in pregnant and nursing rats.